Teaching Conditional Sentence Using Presentation, Practice, Production (PPP) Technique in Vocational School - Arif Widyantoro (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
Learning and understanding conditional sentence for the students are something difficult because it needs carefulness and seriousness. Conditional sentence not only consists of rule to be memorized by students but also consists of meaning that should be understood by students so that many of them feel confused to memorize and understand the rule of conditional sentence. Looking at those problems, the writer chooses PPP technique to overcome those problems. Presentation, Practice, Production (PPP) is one of the techniques that can be used by the teacher to teach conditional sentence because looking at the characteristics of PPP, the writer thinks that PPP technique can overcome those problems. The aims of this study are to describe how to teach conditional sentence using presentation, practice, and production (PPP) and to find out advantages and disadvantages teaching conditional sentence using PPP technique. In writing this paper, the writer uses library research in which the writer collects many sources from books and internet to support the discussion. The result shows that the implementation of teaching conditional sentence using PPP technique is done based on three steps, they are pre teaching, while teaching, and post teaching. The advantages of teaching conditional sentence using PPP technique are (1) Students can develop their own ability in learning conditional sentence, (2) This technique can make students interested in learning process because they are given by the teacher chances to explore their ability(3) The students’ understanding about the material is extensive because they are stimulated to find out or to make sentences, (4) The teacher can modify the learning process by looking at the students’ condition and the difficulties of the material, (5) The PPP approach is relatively straight forward, and structured enough to be easily understood by both students and new or emerging teachers.